Ticking time bombs : ineffective weapons stockpile management in Africa - Institute for Security Studies (South Africa) (Pretoria : Institute for Security Studies, 2011)
Weapons and ammunition explosions at government depots, in particular at military stockpiles across the world, highlight the risks posed by inadequately managed and poorly stored weapons stockpiles. In Africa, the physical risks posed by these stockpiles, and the explosions that occur as a result of them, have left many communities suffering injury and death. While there have been a number of legal and political initiatives adopted to assist African governments in better managing and securing their stockpiles, there are still a range of challenges that contribute to continued explosions occurring on the continent. This paper identifies explosions that have occurred in both Mozambique and Tanzania and assesses the need for African governments to implement and promote more effective stockpile management systems, so as to prevent the occurrence of future risks and explosions.
Introduction -- Historical overview -- United Nations Programme of Action -- SADC Firearms Protocol -- Nairobi Protocol -- Economic Community of West African States (ECOWAS) convention -- Stockpile management initiatives -- Causes of stockpile explosions in Africa -- Measure to improve stockpile management in Africa -- Stockpile management in Africa : case studies -- Mozambique -- Tanzania -- Conclusion and recommendations.
Caption title.
"April 2011."
Includes bibliographical references (p. 10-12).
Also available online in PDF format from Institute for Security Studies web site. Adobe Acrobat Reader required.
Keywords: Ammunition -- Storage -- Africa; Firearms -- Storage -- Africa; Unexploded ordnance -- Africa; Africa -- Armed Forces -- Ordnance and ordnance stores -- Safety measures